Trapped within the law. Will the Kurdish Jews return to their homeland? - Graczyk, Agnieszka (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Jews have lived in Iraq and Kurdistan for thousands of years. The vision of the founding of the State of Israel and the emergence of the Nazi ideology in Europe caused that the participation of Jews in social and cultural life and contribution to the development of education and the economy in Iraq ceased to have meaning. The strong influence of Nazi and anti-Zionist ideology led to discrimination and persecution of the Jewish minority in this country.
Keywords: Kurdish Jews; homeland; Iraqi Kurdistan; islamic state; Mansani